PENGGUNAAN SISTEM SANKSI PIDANA PADA PELAKU TINDAK PIDANA KORPORASI - Ahmad, Ahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The acceptance of the corporation as a subject of criminal law who is considered to be able to commit a criminal act and can be criminally responsible for it will of course lead to other consequences in its application. Various consequences or problems that can arise are reflected in the question of getting a death penalty or imprisonment as regulated in article 10 of the Criminal Code which is applied to a corporation. Or can the “corporate death penalty” and “corporate imprisonment” as stated by Brickey be regarded as a death penalty or imprisonment for a corporation? When compared with the provisions in Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, precisely in article 2 paragraph (2) and article 18 paragraph (1) point c and point d According to this law, in the author's opinion, basically the